Inclusive education approaches in a local context : a practitioner's experience in two elementary schools in Japan : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education in Inclusive Education at Massey University, Palmerston North, New Zealand - Nozue, Akiko (Massey University, 2021)
This qualitative study utilised semi-structured interviews to gain an understanding of the perspectives of an education practitioner who experienced an alternative educational practice implemented in Japan. Being informed by a social constructionism research paradigm, this investigation took a position which was inclined to subjectivism in order to carefully elucidate the full meaning of the practitioners’ voices. The findings suggest a level of alignment between their practice and the inclusive practices discussed in international literature. The enabling factors identified for their practice include a humane approach, the centrality of children’s interests, a sense of security for children and teachers, and teacher agency. Their approach which eventually facilitated an inclusive education for all children suggests a methodological implication to see inclusive education as everyone’s business. Their achievement within Japan’s unique socio-cultural structure sends an encouraging message that inclusive education is possible.
Keywords: 390407 Inclusive education